2009
DOI: 10.1007/s12522-009-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Antireproductive effect of calcium channel blockers on male rats

Abstract: Introduction Drugs have been shown to adversely affect male fertility and recently anti-hypertensive drugs were added to the list. The anti-fertility effects of nifedipine and similar calcium channel blockers are well-illustrated in in vitro experiments but not in vivo. Purpose The present study was designed to experimentally elucidate the sub-chronic effect of nifedipine, verapamil and diltiazem on sperm functions and reproductive hormone levels in vivo. Methods Male rats (150-200 g) were divided into four gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Furthermore, intracellular sodium and calcium levels are critically important for sperm motility, viability, and acrosome reaction. [50][51][52][53][54] It is known that ZNS's mechanisms of action were considered to be its inhibitory effects on voltagegated sodium channel and voltage-sensitive calcium channels. 55,56 Therefore, it could be concluded that the decrease of sperm motility with ZNS administration may be associated with the mechanism of action of this drug including blocking of sodium channels and reducing calcium channel currents.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intracellular sodium and calcium levels are critically important for sperm motility, viability, and acrosome reaction. [50][51][52][53][54] It is known that ZNS's mechanisms of action were considered to be its inhibitory effects on voltagegated sodium channel and voltage-sensitive calcium channels. 55,56 Therefore, it could be concluded that the decrease of sperm motility with ZNS administration may be associated with the mechanism of action of this drug including blocking of sodium channels and reducing calcium channel currents.…”
Section: Discussionmentioning
confidence: 99%
“…Iranloye et al suggested that oral daily administration of 0.57 mg/kg Nif for 30 days causes reversible deleterious effects on sperm function which is not mediated by a change in testosterone secretion (14). Morakinyo et al equally reported that administration of Nif, verapamil, and diltiazem for 30 days appear to have a reversible anti-fertility effect on male rats which does not occur through inhibition of the pituitary-gonadal axis (15).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha‐adrenergic blockers are known to cause retrograde ejaculation and impair sperm concentration and motility . Calcium channel blockers impair sperm motility in vitro , the sperm fertilization process, and overall male fertility . Discontinuation of calcium channel blockers and a switch to alternative antihypertensive drugs should be considered.…”
Section: Discussionmentioning
confidence: 99%